Features of experience of emotional burnout in teachers’ narratives - Tsukhai, Katsiaryna I. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article presents the result of the analysis of the subjective experience obtained during a semi-structured thematic interview of school teachers. The main focus is on their experience of burnout and its verbal description. Different degrees of burnout are reflected in the peculiarities of the teachers’ narrative. The narratives of teachers with a high degree of burnout were characterised by less consistency and integrity of the life plot. An indicator of emotional tension, which is reflected in the experience of teachers, is the inability to connect fragments of the past into a single story, a violation of its sequence. These features were manifested both at the level of individual fragments and at the level of the entire narrative.